From Phocis to Aetolia: Ethnicity and Federalism in Greek Antiquity - THOMAS HUSOY-CIACCIA (2023)
This thesis examines the interrelations between ethnicity and federalism in ancient Greece, focusing on levels of identity. Ethnicity will be investigated as a multi-layered process, particularly underlining regional, sub-regional, and polis-ethnic groups. An ethnosymbolic approach is applied, focusing on myths, festivals, memories, and symbols and their links to ethnicity and federalism in ancient Greece. Four regions make up the chapters of this thesis: 1.Phocis sets up the project, highlighting the significance of sub-regional groups in this region to the end of the Third Sacred War (to 346 BCE).2.Boeotia continues the study as the best documented federal state in Greek antiquity; like the Phocian chapter, it covers the Archaic period to the Third Sacred War.3.Arcadia provides an example of a group with a regional identity that was only federalised briefly in the fourth century. This region is an example of one with strong sub-regional and polis-ethnic groups. Arcadia is examined from the Archaic period to the Battle of Mantinea (362 BCE).4.Aetolia concludes the study as a region that developed from a confederate system in the fifth century to a federal state based on the region’s identity. In the Hellenistic period, the Aetolian federal state expanded beyond its traditional ethnic territory. The period covered in this chapter reaches from the Classical period to the end of the Social War (217 BCE).These chapters investigate the historical development of ethnicity and federalism in these regions using a narrative approach. Various theoretical approaches that have been used to analyse these concepts in the modern world will be applied to Greek antiquity, including McKay’s ethnic matrix, ‘history use’, and ethnofederalism. This thesis combined approaches allow scholars to read between the lines of the ancient evidence and establish an innovative approach to ethnicity and federalism in Greek antiquity.